Evolution of Mercosur intra-regional trade from 2016 to 2020 - Aparecida Bastos, Luciana; Crepaldi, Jesus; Monteiro da Silva, Rodrigo; Bartolomeu de Araújo, Victor Hugo Bartolomeu de Araújo; Pancera, Aline de Queiroz; Iqbal, Badar Alam (Latin American Journal of Trade Policy, 2022)
The first attempts at the Latin American integration process showed a highly pragmatic character, without many concerns for medium and long-term projects. The main concern was to expand intra and extra-regional trade. However, since the 1980s (the decade considered the lost decade for Latin America), when the external debt crises and the adjustment policies recommended by the International Monetary Fund (IMF) led the region to a higher poverty rate due to the social costs of such policies, Latin America has been rethinking its integration. The creation of LAIA (Latin American Integration Association), in 1980, replacing LAFTA (Latin American Free Trade Association), in 1960, and its sub-regional integration have changed Latin America’s economic growth trajectory from the 1990s. Within the scope of LAIA, Mercosur was created in 1991, with the objective of promoting intra and extra-regional trade expansion through the elimination of tariff barriers among its members, implementing a Common External Tariff. The full members of Mercosur are Argentina, Brazil, Paraguay and Uruguay. The bloc also has associated members: Bolivia, Chile, Peru, Colombia, Ecuador, Guyana and Suriname and observer members, namely Mexico and New Zealand. This work was developed to verify whether Mercosur, with the elimination of tariff barriers between full members and the Common External Tariff, has been able to meet its main objective, which is to expand intraregional trade among its members. Therefore, the main objective was to verify whether there was trade expansion between the bloc's full partners between the years 2016 and 2020. The methodologies used for this purpose were descriptive statistics and literature review. Aiming to evaluate the annualized rate of change of trade in the period covered, it was decided to use the Compound Annual Growth Rate (CAGR), which is a differential of this research. The results showed that within the bloc, Brazil had Argentina as its main trading partner. It was observed that there was an expansion of intraregional trade between 2016 and 2018, followed by a considerable reduction of this trade during the period 2019-2020, but that Brazil still continued to be the member that obtained the largest intra-regional trade balances. Paraguay, in turn, did not show the same trend of commercial reduction for all other partners in 2019 and 2020. In addition, in 2020, even with the COVID 19 pandemic, Paraguay managed to increase its exports to Brazil and Argentina, showing a contrary trend only to their exports to Uruguay. Uruguay, in turn, expanded its imports from partners throughout the period, except for Paraguay in 2020, where its exports exceeded imports. With regard to Argentina, its exports to members began to fall in 2019 and increased in 2020, especially in relation to Brazil. The country also drastically reduced its imports from Brazil and Paraguay in 2019 and 2020, although it also considerably expanded imports from Paraguay